Ghrelin Receptor Ligands Reaching Clinical Trials: From Peptides to Peptidomimetics; from Agonists to Antagonists - Vodnik, M.; Štrukelj, B.; Lunder, M. (Hormone and Metabolic Research, 2016)
In the recent decades, great progress has been made in the development of ghrelin receptor ligands. The discovery of the first in vitro only active peptide growth hormone secretagogue derived from Met-enkephalin was the foundation for later discoveries of the receptor and the endogenous ligand ghrelin. Since then, the scope of peptides, peptidomimetics, and small-molecules targeting the ghrelin receptor, GHS-R1a, has expanded dramatically. Numerous agonists have been tested in animals and several in humans, and a handful have progressed to clinical trials for indications such as growth hormone release, gastric emptying, and cachexia. However, with the exception of the approval of GHRP-2 for diagnostic purposes in Japan, none of the candidates have been successfully introduced into the market. More recently, the attention of researchers has been concentrated on developing antagonists and inverse agonists for pharmacological treatment of the ever-expanding obese and overweight population. In this review, we describe the development of GHS-R1a targeting agonists, antagonists, and inverse agonists. We focus on current and completed clinical trials and the therapeutic potential of currently available ligands.
Keywords: GHS-R1a; growth hormone; food intake; gastrointestinal motility